Literary Ecological Analysis in Tere Liye’s Novel “Pulang Pergi” - Hanifah Febria Dwiyanti; Agus Darmuki; Mohammad Kanzunnudin (Attractive : Innovative Education Journal, 2025)
Literary works play an important role as a medium for criticism of environmental degradation and human behavior towards nature. This study aims to analyze the ecological dimensions in Tere Liye's novel Pulang Pergi through the lens of literary ecology. Unlike previous studies, this study specifically explores the integration of ecocultural and ethnoecological concepts in action-crime genre narratives. The method used is descriptive qualitative with Cheryll Glotfelty's ecocritical approach. Data was collected through reading and note-taking techniques, then analyzed using dialectical methods to connect the facts in the text with the reality of the global ecosystem. The results show that the novel Pulang Pergi represents ecological imbalance due to the dominance of technology and destructive human ambition, as reflected in the setting of a nuclear reactor exclusion zone and land exploitation. However, the narrative also offers hope through traditional knowledge and ethnoecology as a path to sustainability. These findings confirm that popular literature can be a critical instrument in voicing contemporary environmental issues and building readers' ecological awareness.